The ground state of deformed nuclei as a boson condensate - Dukelski, J.; Dussel, G. G.; Sofía, H. M. (North-H olland Publishing Company, 1982)
Fil: Dukelski, J. Comisión Nacional de Energía Atómica; Argentina